THE EFFECT OF SERVICE QUALITY AT CND MEULABOH HOSPITAL ON THE SATISFACTION LEVEL OF INPATIENTS PARTICIPATING IN JKN 2024 - Shazia Putri Hazima; Safrizal; Teungku Nih Farisni; Perry Boy Chandra Siahaan; Maiza Duana (RADJA PUBLIKA, 2024)
The influence of service quality on the satisfaction of inpatients participating in National Health Insurance (JKN) is very important to explain. Community demands for quality health services are increasing. Therefore, RSUD must improve the quality of services provided, including dimensions’ tangible, reliability, responsiveness, assurance, and empathy. This study aims to analyze the influence of service quality on the level of satisfaction of inpatients participating in National Health Insurance (JKN) at Cut Nyak Dhien Hospital, Meulaboh. This research used a cross-sectional design with a quantitative approach, data collection techniques via questionnaires, with a population of 7,839 and a sample of 106 inpatient respondents. The research results show that service quality has an important role in determining patient satisfaction. The results of multiple linear regression tests show that service quality simultaneously influences patient satisfaction, with a coefficient of determination of 33.2%. Good service quality can increase patient satisfaction, while poor service quality can reduce patient satisfaction. The results of this research can be used as consideration to improve the quality of service at Cut Nyak Dhien Hospital, Meulaboh and increase the satisfaction of inpatients who are JKN participants.